Theoretical pluralism in psychoanalytic case studies - Willemsen, Jochem; Cornelis, Shana; Geerardyn, Filip M.; Desmet, Mattias; Meganck, Reitske; Inslegers, Ruth; Cauwe, Joachim M. B. D. (Frontiers in Psychology, 2015)
The aim of this study is to provide an overview of the scientific activity of different psychoanalytic schools of thought in terms of the content and production of case studies published on ISI Web of Knowledge. Between March 2013 and November 2013, we contacted all case study authors included in the online archive of psychoanalytic and psychodynamic case studies (www.singlecasearchive.com) to inquire about their psychoanalytic orientation during their work with the patient. The response rate for this study was 45%. It appears that the two oldest psychoanalytic schools, Object-relations psychoanalysis and Ego psychology or ‘Classical psychoanalysis’ dominate the literature of published case studies. However, most authors stated that they feel attached to two or more psychoanalytic schools of thought. This confirms that the theoretical pluralism in psychoanalysis stretches to the field of single case studies. The single case studies of each psychoanalytic school are described separately in terms of methodology, patient, therapist, or treatment features. We conclude that published case studies features are fairly similar across different psychoanalytic schools. The results of this study are not representative of all psychoanalytic schools, as some do not publish their work in ISI ranked journals.